MENGUKUR TINGKAT LIKUIDITAS, PROFITABILITAS DAN AKTIVITAS PERUSAHAAN - I Made Sudana; Istiarto Istiarto (Valid: Jurnal Ilmiah, 2016)
Company as an organization aspires added value factor, production factor will not escape the economic conditions. The state of the economy of a country or a nation will affect the income per capita, which may also affect the development of the company. The development of an enterprise can be seen from the performance of the company, which usually can be analyzed from its financial statement. Research conducted at company X for which data are taken from secondary data such as financial statements in 2014 and 2015, is one of the companies engaged in food whose shares are already listed on the stock exchange. The results of the analysis of financial statements that can be concluded from the analysis of liquidity (Current Ratio, Quick Ratio and Cash Ratio) from 2014 to 2015 showed kaikan of 219, 42% to 232.60%, profitability analysis (Profit Margin Ratio, ROA, ROI and ROE) of ear 2014 to 2015 shows an increase Profit Margin of 11.47% to 12.67%, ROA of 13.76% to 15.09%, ROI of 10.56% to 11.28% and ROE of 18, 13% to 18.31%. Activity ratio (TATO, receivable AVERAGE, AVERAGE DAYS INVENTORY) from 2014 to 2015 showed an increase from 43 days to 46 days, the average inventory in the warehouse. Based on the analysis concludes enterprise performance X measured from the liquidity, profitability and activity showed a pretty good improvement